S96 An open-label extension (ext) study of lumacaftor/ivacaftor (lum/iva) therapy in patients aged 6 to 11 years with cystic fibrosis (cf) homozygous for f508del-cftr. (15th November 2017) - Chilvers, M; Tian, S; Marigowda, G; Bsharat, M; Hug, C; Solomon, M; Black, P; Rosenfeld, M; Sawicki, G; Hoppe, J
Abstract : Objective: Lumacaftor/Ivacaftor (LUM/IVA) was well tolerated and had beneficial effects on lung function, sweat chloride (SwCl), and body mass index (BMI) in a 24 week, open-label study (VX15–809–011B [011B]) in patients aged 6 to 11 years with cystic fibrosis (CF) homozygous for F508del . We report 36 weeks of additional safety and efficacy data in an ongoing 96 week extension (EXT) study (VX15–809–110; NCT02544451 ). Methods: Eligible patients from 011B received LUM 200 mg/IVA 250 mg every 12 hours (q12h; 6–11 years) or LUM 400 mg/IVA 250 mg q12h (≥12 years). Primary endpoint was safety. Secondary endpoints included changes in SwCl and lung clearance index based on lung volume turnover required to reach 2.5% of starting N2 concentration (LCI2.5 ) through week 24, and BMI and percent predicted FEV1 (ppFEV1 ) through week 36. Results: Of the 49 enrolled patients (mean age [SD], 9.2 [1.48] years), 47 completed 36 weeks of the EXT study. Adverse events (AEs) were reported in 91.8% of patients (34.7% mild; 49.0% moderate). Common AEs (cough, n=18; infective pulmonary exacerbation, n=18) were consistent with expected CF manifestations. Eight (16.3%) patients had serious AEs. Four (8.2%) patients had ≥1 respiratory AE (2 wheezing; 1 bronchial hyperreactivity; 1 dyspnea; 1 respiration abnormal). Six (12.2%) patients had elevated alanine aminotransferase or aspartate aminotransferase (≥3 to 5×upper limit of normal [ULN], n=3;≥5 to 8×ULN, n=1;≥8× ULN, n=2). No drug discontinuations were due to AEs. Changes from 011B baseline (BL) in ppFEV1 and SwCl were similar to those at 011B week 24 (Table). BMI continued to improve. LCI2.5 improvements were stable through EXT week 4 (n=18); values at EXT week 24 in a reduced sample size (n=12) were similar to those at 011B BL. Conclusion: LUM/IVA was well tolerated for up to 60 weeks in patients aged 6 to 11 years, with no new safety concerns compared with previous LUM/IVA studies conducted in this patient population. LUM/IVA was associated with improved BMI and maintenance of lung function. Please refer to page A257 for declarations of interest in relation to abstract S96.